Poverty and Health Outcomes ın Nigeria - Ubi, Peter; Ndem, Bassey (International Journal of Economics and Financial Issues, 2019)
The study models the dynamics of poverty as they affect health outcomes in Nigeria. Vector autoregressive econometric approach was used to examine whether health outcomes (life expectancy and ınfant mortality rate) in Nigeria respond to poverty shock. Empirical evidence from the study indicates that poverty shock does not have any significant impact on health outcome variables. Specifically, variations in health outcomes are not actually due to poverty shocks but due to the health outcome shock. It is therefore recommended that improvement in health outcome of the population is a necessity to poverty reduction in Nigeria. Keywords: Poverty, Health, Outcomes, Vicious JEL Classifications: I12, I32 DOI: https://doi.org/10.32479/ijefi.8704